Stone composite adhesive and its preparation method and application
By using pre-promoting epoxy vinyl ester resin and dimer acid modified epoxy vinyl ester resin composition and adding phosphate esters and other components, a stone composite glue with fast curing speed and high bonding strength was prepared, which solved the problems of low construction efficiency and insufficient bonding strength in the prior art. It is suitable for bonding of a variety of stone materials and other materials, and has good flame retardant properties.
Patent Information
- Application Number
- CN202411984139.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Existing stone composite glues cannot take into account both the curing speed and the bonding strength, resulting in low construction efficiency and insufficient bonding strength.
Pre-promoting epoxy vinyl ester resin and pre-promoting dimer acid modified epoxy vinyl ester resin composition are used as the main resin, and phosphate esters, thixotropic agents, silane coupling agents and fillers are added. Through specific ratios and process treatments, a stone composite glue with fast curing speed and high bonding strength is prepared.
It achieves the effect of fast curing speed and high bonding strength. It is suitable for stone and vitrified bricks with high density, high hardness, hydrophobic and smooth bonding, as well as their bonding with other materials, and has good flame retardant properties.
Smart Images

Figure BDA0005222183450000021 
Figure BDA0005222183450000051 
Figure BDA0005222183450000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stone adhesives, and in particular to a stone composite adhesive and a preparation method and application thereof. Background Art
[0002] At present, the main stone composite adhesives on the market are epoxy resin systems and unsaturated resin systems. Epoxy resin system composite adhesives are widely used in various fields due to their high bonding performance, but they have a long curing time and require a long waiting time during the construction process. They are not suitable for assembly line operations and affect construction efficiency. In addition, epoxy resin has high viscosity, and the market often uses the method of adding diluents to reduce the viscosity of the product, but the addition of diluents will reduce the mechanical properties of the product, resulting in many defects such as weak adhesion to the surface of stone or other substrates. Unsaturated resin system stone composite adhesives have the advantages of fast curing speed and are widely used in the conventional stone bonding industry. However, for stones with high bonding density, high hardness, hydrophobic and smooth surfaces, such as rock slabs, artificial stones, vitrified tiles, etc., the bonding strength is insufficient or even falls off.
[0003] The patent application with publication number CN116042154A discloses an adhesive for stone slab composite, its preparation method and application, which can be used for bonding between stones and between stones and other materials. However, due to the epoxy resin system, the curing time at 25°C requires more than 2 hours, and the construction efficiency is very low. Summary of the invention
[0004] In order to overcome the deficiencies of the above-mentioned technologies, the purpose of the present invention is to provide a stone composite adhesive and a preparation method and application thereof, so as to solve the problem that the existing stone adhesive cannot take into account both the curing speed and the bonding strength.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A stone composite adhesive comprises component one and component two; the special feature of the invention is that component one comprises the following ingredients by weight: 60-90 parts of pre-accelerated epoxy vinyl ester resin, 10-40 parts of pre-accelerated dimer acid-modified epoxy vinyl ester resin, 0.5-5 parts of phosphate, 5-12 parts of thixotropic agent, 0.5-3 parts of silane coupling agent and 30-150 parts of filler; component two comprises a curing agent. Epoxy vinyl ester resin is an excellent thermosetting polymer material with good processability and mechanical properties, and has been widely used in the fields of industry, agriculture, national defense, etc. However, the sliding range between molecular chains of epoxy vinyl ester resin is small, resulting in insufficient toughness and strength of the cured product. Using dimer acid-modified epoxy vinyl ester resin can improve the toughness of the resin cured product, but the strength is still slightly insufficient. The main resin of the present invention selects a pre-accelerated epoxy vinyl ester resin and a pre-accelerated dimer acid-modified epoxy vinyl ester resin composition. The resin composition can improve flexibility and significantly improve bonding strength when bonding high-density, high-hardness, hydrophobic and smooth stone materials such as rock slabs, artificial stones, vitrified tiles, etc. The effect of compounding the two is significantly better than that of using only a single resin.
[0007] As a preferred embodiment, the weight ratio of component one to component two is 100:2-4.
[0008] As a preferred embodiment, the pre-promoted dimer acid-modified epoxy vinyl ester resin has the following general structural formula:
[0009]
[0010] Among them, R1 is
[0011] n=0~2
[0012] or
[0013] n = 0 to 2;
[0014] R2 is H or -CH3.
[0015] The pre-accelerated dimer acid-modified epoxy vinyl ester resin has hydroxyl groups and allyl groups in its molecular structure. The hydroxyl groups can enhance wettability, and the allyl groups can achieve cross-linking between the pre-accelerated dimer acid-modified epoxy vinyl ester resin.
[0016] As a preferred embodiment, the preparation method of the pre-promoted dimer acid-modified epoxy vinyl ester resin comprises the following steps:
[0017] 1) Stir and heat the dimer acid-modified epoxy resin, add a catalyst and a polymerization inhibitor, dropwise add acrylic acid monomer, then heat to 90-130° C., react until the acid value reaches 20±5 mg KOH / g, and then cool the reaction system to 70-80° C.;
[0018] 2) adding styrene and accelerator to the reaction system after cooling and dissolving them uniformly to obtain the pre-accelerated dimer acid-modified epoxy vinyl ester resin.
[0019] Furthermore, the dimer acid-modified epoxy resin includes any one of a dimer acid-modified bisphenol A epoxy resin and a dimer acid-modified bisphenol F epoxy resin.
[0020] Furthermore, the molar ratio of the dimer acid-modified epoxy resin to the acrylic monomer is 1:2.1 to 2.2.
[0021] Furthermore, the catalyst includes any one or more of benzyltriethylammonium chloride, benzyldimethylamine, and tetrabutylammonium bromide; the amount of the catalyst used is 0.5-1wt% of the total amount of the dimer acid-modified epoxy resin and the acrylic acid monomer.
[0022] Furthermore, the polymerization inhibitor includes any one or more of hydroquinone, methyl hydroquinone, and tert-butyl hydroquinone; the dosage of the polymerization inhibitor is 0.02-0.1wt% of the total amount of the dimer acid-modified epoxy resin and the acrylic monomer.
[0023] Furthermore, the acrylic acid monomer includes any one of acrylic acid and methacrylic acid.
[0024] Furthermore, the accelerator includes any one or two of dimethylaniline and dimethyl-p-toluidine; the amount of the accelerator is 0.3-0.8wt% of the total amount of the pre-accelerated dimer acid-modified epoxy vinyl ester resin.
[0025] Furthermore, the solid content of the pre-accelerated dimer acid-modified epoxy vinyl ester resin is 50-70%.
[0026] As a preferred embodiment, the phosphate ester includes one or more of methacryloyloxyethyl phosphate, bis(2-(methacryloyloxy)ethyl) phosphate, methacrylate phosphate, and polyethylene glycol methacrylate phosphate. It is found through experiments that the addition of phosphate ester can not only further improve the bonding strength between stones with high density, high hardness, hydrophobic and smooth surfaces, but also significantly improve the bonding strength between stones and other materials such as steel, iron, and wood. In addition, at high temperatures, the phosphate group will decompose to form a protective layer that can isolate oxygen and heat and prevent the spread of flames, thereby making the stone composite adhesive have a flame retardant effect.
[0027] As a preferred embodiment, the thixotropic agent includes fumed silica.
[0028] As a preferred embodiment, the silane coupling agent includes any one or more of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.
[0029] As a preferred embodiment, the filler includes any one or more of calcium carbonate, activated calcium carbonate, silicon dioxide, and aluminum hydroxide.
[0030] As a preferred embodiment, the curing agent includes dibenzoyl peroxide.
[0031] As a preferred embodiment, the component one includes the following ingredients in parts by weight: 75-85 parts of pre-accelerated epoxy vinyl ester resin, 15-25 parts of pre-accelerated dimer acid-modified epoxy vinyl ester resin, 1-5 parts of phosphate ester, 5-10 parts of thixotropic agent, 1-3 parts of silane coupling agent and 50-150 parts of filler.
[0032] As a preferred embodiment, the component one includes the following ingredients in parts by weight: 80 parts of pre-accelerated epoxy vinyl ester resin, 20 parts of pre-accelerated dimer acid-modified epoxy vinyl ester resin, 1.5 parts of bis(2-(methacryloyloxy)ethyl) phosphate, 0.5 parts of polyethylene glycol methacrylate phosphate, 7 parts of fumed silica, 0.7 parts of γ-methacryloyloxypropyltrimethoxysilane, 0.8 parts of vinyltrimethoxysilane, 35 parts of calcium carbonate, 35 parts of silica, and 40 parts of aluminum hydroxide.
[0033] The present invention also provides a method for preparing the stone composite adhesive, comprising the following steps:
[0034] 1) 60-90 parts of pre-accelerated epoxy vinyl ester resin, 10-40 parts of pre-accelerated dimer acid-modified epoxy vinyl ester resin, 0.5-5 parts of phosphate ester, 5-12 parts of thixotropic agent, 0.5-3 parts of silane coupling agent and 30-150 parts of filler are mixed at room temperature with high-speed stirring to obtain component 1;
[0035] 2) Add the curing agent to component one, mix and stir at room temperature to obtain the stone composite adhesive.
[0036] As a preferred solution, high-speed stirring is performed using a high-speed stirrer with a stirring speed of 1000-1500 rpm.
[0037] The present invention also provides an application of stone composite glue in the bonding of stone or vitrified tile; its special features are: the stone composite glue is the above-mentioned stone composite glue or the stone composite glue prepared by the above-mentioned preparation method; the stone includes rock slab; the bonding includes the bonding of stone and stone, stone and wood, stone and steel, vitrified tile and vitrified tile, and vitrified tile and steel.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The stone composite adhesive provided by the present invention can take into account both curing speed and bonding strength, and has the advantages of fast curing speed and high bonding strength. It can be used for bonding between stones and between stones and other materials, between vitrified tiles and between vitrified tiles and between vitrified tiles and other materials. It is particularly suitable for bonding between materials with high density, high hardness, and hydrophobic and smooth properties such as rock slabs and vitrified tiles, as well as between these and other materials.
[0040] The main resin of the present invention adopts pre-accelerated epoxy vinyl ester resin and pre-accelerated dimer acid modified epoxy vinyl ester resin composition. The resin composition can improve flexibility and significantly improve bonding strength when bonding high-density, high-hardness, hydrophobic and smooth stone materials.
[0041] The addition of phosphate ester in the present invention can not only further improve the bonding strength between stone and vitrified tiles, but also significantly improve the bonding strength between stone, vitrified tiles and other materials such as steel, iron, and wood; in addition, the phosphate ester group will decompose at high temperature to form a protective layer, which can isolate oxygen and heat and prevent the spread of flames, thereby effectively improving the flame retardant effect of the stone composite adhesive. DETAILED DESCRIPTION
[0042] In order to better explain the present invention, the main contents of the present invention are further explained below in conjunction with specific embodiments, but the contents of the present invention are not limited to the following embodiments.
[0043] The invention provides a stone composite adhesive, comprising component one and component two; component one comprises the following ingredients in parts by weight: 60-90 parts of pre-accelerated epoxy vinyl ester resin, 10-40 parts of pre-accelerated dimer acid-modified epoxy vinyl ester resin, 0.5-5 parts of phosphate ester, 5-12 parts of thixotropic agent, 0.5-3 parts of silane coupling agent and 30-150 parts of filler; component two comprises a curing agent.
[0044] The weight ratio of component one to component two is 100:2-4.
[0045] The pre-promoted dimer acid modified epoxy vinyl ester resin has the following general structural formula:
[0046]
[0047] Among them, R1 is
[0048] n=0~2
[0049] or
[0050] n = 0 to 2;
[0051] R2 is H or -CH3.
[0052] The preparation method of the above-mentioned pre-promoted dimer acid-modified epoxy vinyl ester resin comprises the following steps:
[0053] 1) Stir and heat the dimer acid-modified epoxy resin, add a catalyst and a polymerization inhibitor, dropwise add acrylic acid monomer, then heat to 90-130° C., react until the acid value reaches 20±5 mg KOH / g, and then cool the reaction system to 70-80° C.;
[0054] 2) adding styrene and accelerator to the reaction system after cooling and dissolving them uniformly to obtain the pre-accelerated dimer acid-modified epoxy vinyl ester resin.
[0055] The dimer acid-modified epoxy resin includes any one of a dimer acid-modified bisphenol A type epoxy resin and a dimer acid-modified bisphenol F type epoxy resin.
[0056] The molar ratio of dimer acid modified epoxy resin to acrylic monomer is 1:2.1-2.2.
[0057] The catalyst comprises any one or more of benzyltriethylammonium chloride, benzyldimethylamine and tetrabutylammonium bromide; the amount of the catalyst is 0.5-1wt% of the total amount of the dimer acid-modified epoxy resin and the acrylic acid monomer.
[0058] The polymerization inhibitor includes any one or more of hydroquinone, methyl hydroquinone and tert-butyl hydroquinone; the dosage of the polymerization inhibitor is 0.02-0.1wt% of the total amount of the dimer acid-modified epoxy resin and the acrylic acid monomer.
[0059] The acrylic monomer includes any one of acrylic acid and methacrylic acid.
[0060] The accelerator comprises any one or two of dimethylaniline and dimethyl-p-toluidine; the amount of the accelerator is 0.3-0.8wt% of the total amount of the pre-accelerated dimer acid-modified epoxy vinyl ester resin.
[0061] The solid content of the pre-accelerated dimer acid-modified epoxy vinyl ester resin is 50-70%.
[0062] The preparation method of the stone composite adhesive comprises the following steps:
[0063] 1) 60-90 parts of pre-accelerated epoxy vinyl ester resin, 10-40 parts of pre-accelerated dimer acid-modified epoxy vinyl ester resin, 0.5-5 parts of phosphate ester, 5-12 parts of thixotropic agent, 0.5-3 parts of silane coupling agent and 30-150 parts of filler are stirred and mixed at high speed (rotation speed 1000-1500 rpm) at room temperature to obtain component 1;
[0064] 2) Add the curing agent to component 1, mix and stir at room temperature to obtain the stone composite adhesive of the present invention.
[0065] Room temperature is the ambient temperature, preferably an ambient temperature above -10°C.
[0066] The phosphate ester includes one or more of methacryloyloxyethyl phosphate, bis(2-(methacryloyloxy)ethyl) phosphate, methacrylate phosphate, and polyethylene glycol methacrylate phosphate.
[0067] The thixotropic agent includes fumed silica; and the curing agent includes dibenzoyl peroxide.
[0068] The silane coupling agent includes any one or more of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.
[0069] The filler includes any one or more of calcium carbonate, activated calcium carbonate, silicon dioxide and aluminum hydroxide.
[0070] The invention also provides application of the stone composite adhesive in bonding stone and vitrified tiles.
[0071] The present invention is further described below by means of specific examples S1 to 22 and comparative examples D1 to 12.
[0072] The composition ratios of the components of the stone composite adhesive component 1 in Examples S1 to 22 and Comparative Examples D1 to 10 are shown in Table 1, and the composition and reaction conditions of the reactants in the pre-promoted dimer acid-modified epoxy vinyl ester resin in the stone composite adhesive component 1 in Examples S1 to 22 and Comparative Examples D2 and D4 to 10 are shown in Table 2.
[0073] In Table 1, A: pre-accelerated epoxy vinyl ester resin; B: pre-accelerated dimer acid modified epoxy vinyl ester resin; C1: methacryloyloxyethyl phosphate; C2: bis(2-(methacryloyloxy)ethyl) phosphate; C3: methacrylate phosphate; C4: polyethylene glycol methacrylate phosphate; D: fumed silica; E1: γ-methacryloyloxypropyltrimethoxysilane; E2: vinyltrimethoxysilane; E3: vinyltriethoxysilane; F1: calcium carbonate; F2: activated calcium carbonate; F3: silica; F4: aluminum hydroxide.
[0074] Table 1: Proportions of the components of the stone composite adhesive component 1 in Examples S1-22 and Comparative Examples D1-10
[0075]
[0076] Table 2: Compositions and reaction conditions of reactants in the pre-promoted dimer acid-modified epoxy vinyl ester resin in the first component of the stone composite adhesive in Examples S1 to S22 and Comparative Examples D2, D4 to 10
[0077]
[0078] In Table 2: the contents of catalyst, inhibitor and promoter are all percentages of the total amount of dimer acid modified epoxy resin and acrylic monomer; G1: dimer acid modified bisphenol A type epoxy resin; G2: dimer acid modified bisphenol F type epoxy resin; H1: methacrylic acid; H2: acrylic acid; I1: benzyltriethylammonium chloride; I2: benzyldimethylamine; I3: tetrabutylammonium bromide; J1: hydroquinone; J2: methyl hydroquinone; J3: tert-butyl hydroquinone; K1: dimethylaniline; K2: dimethyl-p-toluidine.
[0079] The structure of the pre-promoted dimer acid-modified epoxy vinyl ester resin B in Examples S1 to 22 and Comparative Examples D2 and D4 to 10 is as follows:
[0080] When dimer acid-modified bisphenol A type epoxy resin (G1) and methacrylic acid (H1) are used to prepare pre-accelerated dimer acid-modified epoxy vinyl ester resin, in the structural formula of the pre-accelerated dimer acid-modified epoxy vinyl ester resin, R1 is
[0081] n = 0 to 2;
[0082] R2 is -CH3.
[0083] When dimer acid-modified bisphenol F type epoxy resin (G2) and methacrylic acid (H1) are used to prepare pre-accelerated dimer acid-modified epoxy vinyl ester resin, in the structural formula of the pre-accelerated dimer acid-modified epoxy vinyl ester resin, R1 is
[0084] n = 0 to 2;
[0085] R2 is -CH3.
[0086] When dimer acid-modified bisphenol A type epoxy resin (G1) and acrylic acid (H2) are used to prepare pre-accelerated dimer acid-modified epoxy vinyl ester resin, in the structural formula of the pre-accelerated dimer acid-modified epoxy vinyl ester resin, R1 is:
[0087] n = 0 to 2;
[0088] R2 is -H.
[0089] When dimer acid-modified bisphenol F type epoxy resin (G2) and acrylic acid (H2) are used to prepare pre-accelerated dimer acid-modified epoxy vinyl ester resin, in the structural formula of the pre-accelerated dimer acid-modified epoxy vinyl ester resin, R1 is:
[0090] n = 0 to 2;
[0091] R2 is -H.
[0092] The stone composite adhesives of Examples S1-22 and Comparative Examples D1-12 were used for composite bonding, and the performance of the composite adhesives was tested. The test results are shown in Table 3.
[0093] Table 3: Performance test data of stone composite adhesives of Examples S1 to 22 and Comparative Examples D1 to 12
[0094]
[0095]
[0096] Among them, comparative example D11 is a commercially available marble glue, whose component is unsaturated resin glue; comparative example D12 is an adhesive in the Chinese invention application with application number CN202211686101.X.
[0097] In Examples S1-22 and Comparative Examples D1-11, 100 parts by weight of component 1 and 3 parts by weight of curing agent dibenzoyl peroxide are mixed and then used. In Examples S1-22 and Comparative Examples D1-10, during the preparation of the pre-accelerated dimer acid-modified epoxy vinyl ester resin, the reaction system is cooled to 75° C. before adding styrene and the accelerator. During the preparation of component 1, a high-speed stirrer is used for stirring and mixing, and the stirring speed is 1500 rpm.
[0098] The stone composite adhesive obtained in Examples S1 to 22 of the present invention and Comparative Examples D1 to 12 were respectively subjected to performance tests, and the test parameters included curing time, impact toughness, bending elastic modulus, tensile shear (stainless steel-stainless steel), compressive shear (stone-stone, stone-wood, rock slab-rock slab, rock slab-stainless steel), and oxygen index. The test results are shown in Table 3.
[0099] The specific methods of each test are as follows:
[0100] Curing time determination method:
[0101] Examples S1-22 and Comparative Examples D1-11: 100 parts by weight of component 1 were added with 3 parts by weight of curing agent dibenzoyl peroxide of component 2, mixed and stirred evenly, and the curing time was tested;
[0102] Comparative Example D12: Components A and B of epoxy stone board composite adhesive were mixed at a ratio of 2:1 and stirred evenly, and the curing time was tested. The performance test results refer to the Chinese invention application with application number CN202211686101.X.
[0103] Impact toughness, flexural modulus, tensile shear, and compressive shear: refer to the JC / T989-2016 test method, prepare the solidified sample, and then use a universal tensile testing machine for testing.
[0104] Oxygen index: Test the oxygen index of the cured product according to GB / T 2046-2009 "Determination method of oxygen index".
[0105] As shown in Table 3, the stone composite adhesives of Examples S1 to 22 of the present invention are much higher than those of Comparative Example D12 in terms of gel time, tensile shear, and compressive shear. The stone composite adhesive provided by the present invention has the advantages of short curing time and high bonding strength. Among them, the composite adhesives of Examples S5, 6, 7, 8, 11, 12, and 13 have high compressive shear strength after bonding various materials, and other performance parameters are also high, which are preferred embodiments. Among them, the composite adhesive of Example S12 is more prominent, which has a short curing time, high tensile shear strength, and its performance in bonding various materials is also higher than that of other embodiments.
[0106] In addition, combined with the performance test results of the adhesives of Comparative Examples D1-2 (single resin, stone composite adhesive without adding phosphate ester), Comparative Examples D3-4 (single resin, stone composite adhesive with adding phosphate ester), Comparative Examples D5-10 (the relevant components are outside the scope of the present invention), Comparative Example D11 (commercially available marble adhesive, i.e., unsaturated resin adhesive), and Comparative Example D12 shown in Table 3, the following analysis is made:
[0107] (1) Comparative Examples D1 and D2 are adhesives made of a single pre-accelerated resin without adding phosphate, and the other components of which are the same as those of Example S1. Comparative Example D1 uses a pre-accelerated epoxy vinyl ester resin, and Comparative Example D2 uses a single pre-accelerated dimer acid-modified epoxy vinyl ester resin. The epoxy vinyl ester resin modified with dimer acid in the present invention can improve the impact toughness of the resin cured product, but the bending elastic modulus decreases significantly. Although the compressive shear strength between the stone and other substrates is slightly enhanced, the bonding strength is still not ideal.
[0108] (2) Comparative Examples D3 and D4 are based on Comparative Examples D1 and D2, with phosphate ester added, and other components remain the same. On the basis of a single resin component, after adding phosphate ester, although the bonding strength between high-density, high-hardness, hydrophobic and smooth stones (rock slab-rock slab) can be slightly improved, and the bonding strength between stone and other materials such as stone, stainless steel, and wood can be slightly improved, but the increase in colloidal bonding strength is limited by adding phosphate ester alone.
[0109] (3) The present invention prepares a stone composite adhesive by compounding pre-accelerated epoxy vinyl ester resin and pre-accelerated dimer acid modified epoxy vinyl ester resin in a certain proportion as the main resin, and reasonably compounding methacryloyloxyethyl phosphate, bis(2-(methacryloyloxy)ethyl) phosphate, methacrylate phosphate, and polyethylene glycol methacrylate phosphate. As shown in Table 3, the composite adhesive of the present invention has greatly improved the bonding strength between conventional stones, between high-density, high-hardness, hydrophobic and smooth stones, between vitrified tiles, and between stones and other materials such as stainless steel and wood, while ensuring the curing time. It not only retains the advantage of short curing time, but also greatly improves the bonding strength between stones, between vitrified tiles, and between stones and other materials such as stainless steel and wood.
[0110] (4) In comparative examples D5-6, pre-accelerated epoxy vinyl ester resin and pre-accelerated dimer acid-modified epoxy vinyl ester resin are compounded as the main resin, but the compounding ratio is outside the scope of the present invention. Experimental data show that when the proportion of pre-accelerated dimer acid-modified epoxy vinyl ester resin is less than 10% of the main resin, the impact toughness enhancement effect is not obvious; when the proportion of pre-accelerated dimer acid-modified epoxy vinyl ester resin is greater than 90% of the main resin, the toughness enhancement effect is obvious, but the bending elastic modulus decreases greatly, and the improvement effect is not achieved.
[0111] (5) The amount of phosphate added in Comparative Examples D7-8 is outside the scope of the present invention. Experimental data show that when the proportion of phosphate is less than 0.5% of the main resin, the bonding performance between stone and wood, rock board and rock board, and rock board and steel is not significantly improved; when the proportion of phosphate is greater than 7.0% of the main resin, the bonding performance between the above composite materials is improved, but the increase rate is reduced.
[0112] (6) Comparative Examples D9-10 are filler additions outside the scope of the present invention. Experimental data show that adding fillers within a reasonable range helps to enhance the bonding performance of the composite adhesive, but when the proportion of fillers is less than 30% of the main resin, the enhancement effect is not obvious; when the proportion of fillers is greater than 150% of the main resin, the content of the colloidal resin decreases significantly and the bonding performance drops significantly.
[0113] (7) Comparative Example D11 is a commercially available marble glue, i.e., an unsaturated resin adhesive. Marble glue has the characteristics of fast curing speed and can meet the bonding requirements between conventional stones. However, the bonding strength between high-density, high-hardness, hydrophobic and smooth materials (rock slab-rock slab, vitrified tile-vitrified tile), and between stone and other materials such as stainless steel and wood is very poor.
[0114] (8) Compared with conventional stone adhesives, the stone composite adhesive of the present invention can effectively improve the flame retardant effect.
[0115] The following experiments further verify the flame retardant effect after adding phosphate. The experiment is divided into seven groups. In the first to sixth groups, component one includes 70 parts of pre-accelerated epoxy vinyl ester resin, 30 parts of pre-accelerated dimer acid modified epoxy vinyl ester resin, 3 parts of phosphate, 8 parts of fumed silica, 1 part of vinyl trimethoxy silane, and 50 parts of aluminum hydroxide; component two includes 3 parts of dibenzoyl peroxide, and the specific composition of phosphate is shown in Table 4. The oxygen index of the verification example was tested according to GB / T 2046-2009 "Determination of Oxygen Index Method", and the results are shown in Table 4.
[0116] The first group used methacryloyloxyethyl phosphate; the second group used bis(2-(methacryloyloxy)ethyl) phosphate; the third group used methacrylic acid phosphate; the fourth group used polyethylene glycol methacrylic acid phosphate; the fifth group used methacryloyloxyethyl phosphate and bis(2-(methacryloyloxy)ethyl) phosphate in a weight ratio of 1:1; the sixth group used methacryloyloxyethyl phosphate, bis(2-(methacryloyloxy)ethyl) phosphate and methacrylic acid phosphate in a weight ratio of 1:1:1. The seventh group used styrene as an active diluent to replace phosphate.
[0117] Grouping one two three Four five six Styrene Oxygen index (%) 26.1 27.5 26.7 27.0 28.6 28.1 21.0
[0118] Experiments have shown that adding phosphate esters can effectively improve the flame retardant effect of cured resins. Phosphate ester groups will decompose at high temperatures to form a protective layer that can isolate oxygen and heat and prevent the spread of flames.
[0119] In summary, the stone composite adhesive of the present invention takes into account both curing speed and bonding strength, and has the advantages of fast curing speed, high bonding strength, wide application range and good flame retardant performance. It is particularly suitable for bonding between high-density, high-hardness, hydrophobic and smooth materials (rock slab-rock slab, vitrified tile-vitrified tile), as well as between stone or vitrified tile and other materials such as stainless steel and wood.
[0120] The embodiments of the present invention are only preferred implementation schemes and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0121] Other parts not described belong to the prior art.
Claims
1. A stone composite adhesive, comprising component one and component two; characterized in that: The component one comprises the following ingredients in parts by weight: 60 to 90 parts of pre-accelerated epoxy vinyl ester resin, 10 to 40 parts of pre-accelerated dimer acid-modified epoxy vinyl ester resin, 0.5 to 5 parts of phosphate ester, 5 to 12 parts of thixotropic agent, 0.5 to 3 parts of silane coupling agent and 30 to 150 parts of filler; the component two comprises a curing agent.
2. The stone composite adhesive according to claim 1, characterized in that: The pre-promoted dimer acid-modified epoxy vinyl ester resin has the following general structural formula: Among them, R1 is R2 is H or -CH3.
3. The stone composite adhesive according to claim 1, characterized in that: The preparation method of the pre-promoted dimer acid-modified epoxy vinyl ester resin comprises the following steps: 1) Stirring and heating the dimer acid-modified epoxy resin, adding a catalyst and a polymerization inhibitor, dropping an acrylic acid monomer, and then heating to 90-130° C., reacting until the acid value reaches 20±5 mg KOH / g, and then cooling the reaction system to 70-80° C.; 2) adding styrene and accelerator to the reaction system after cooling and dissolving them evenly to obtain the pre-accelerated dimer acid-modified epoxy vinyl ester resin.
4. The stone composite adhesive according to claim 3, characterized in that: The dimer acid modified epoxy resin includes any one of dimer acid modified bisphenol A epoxy resin and dimer acid modified bisphenol F epoxy resin; the molar ratio of the dimer acid modified epoxy resin to the acrylic monomer is 1:2.1-2.2; the catalyst includes any one or more of benzyltriethylammonium chloride, benzyldimethylamine, and tetrabutylammonium bromide; the amount of the catalyst is 0.5-1wt% of the total amount of the dimer acid modified epoxy resin and the acrylic monomer; the inhibitor includes any one or more of hydroquinone, methyl hydroquinone, and tert-butyl hydroquinone; the amount of the inhibitor is 0.02-0.1wt% of the total amount of the dimer acid modified epoxy resin and the acrylic monomer; the acrylic monomer includes any one of acrylic acid and methacrylic acid; the accelerator includes any one or two of dimethylaniline and dimethyl-p-toluidine; the amount of the accelerator is 0.3-0.8wt% of the total amount of the pre-promoted dimer acid modified epoxy vinyl ester resin.
5. The stone composite adhesive according to claim 3, characterized in that: The solid content of the pre-accelerated dimer acid-modified epoxy vinyl ester resin is 50-70%.
6. The stone composite adhesive according to claim 1, characterized in that: The phosphate ester includes one or more of methacryloyloxyethyl phosphate, bis(2-(methacryloyloxy)ethyl) phosphate, methacrylate phosphate, and polyethylene glycol methacrylate phosphate.
7. The stone composite adhesive according to claim 1, characterized in that: The silane coupling agent includes any one or more of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane; the filler includes any one or more of calcium carbonate, activated calcium carbonate, silicon dioxide, and aluminum hydroxide; the thixotropic agent includes fumed silica; and the curing agent includes dibenzoyl peroxide.
8. The stone composite adhesive according to any one of claims 1 to 7, characterized in that: The first component comprises the following ingredients in parts by weight: 75-85 parts of pre-accelerated epoxy vinyl ester resin, 15-25 parts of pre-accelerated dimer acid-modified epoxy vinyl ester resin, 1-5 parts of phosphate ester, 5-10 parts of thixotropic agent, 1-3 parts of silane coupling agent and 50-150 parts of filler.
9. The method for preparing the stone composite adhesive according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) 60-90 parts of pre-accelerated epoxy vinyl ester resin, 10-40 parts of pre-accelerated dimer acid-modified epoxy vinyl ester resin, 0.5-5 parts of phosphate ester, 5-12 parts of thixotropic agent, 0.5-3 parts of silane coupling agent and 30-150 parts of filler are mixed at room temperature with high-speed stirring to obtain component 1; 2) Add the curing agent to component one, mix and stir at room temperature to obtain the stone composite adhesive.
10. Application of a stone composite adhesive in bonding stone or vitrified tiles, characterized in that: The stone composite adhesive is the stone composite adhesive described in any one of claims 1 to 8 or the stone composite adhesive prepared by the preparation method described in claim 9; the stone includes rock slabs; the bonding includes bonding between stone and stone, stone and wood, stone and steel, vitrified brick and vitrified brick, and vitrified brick and steel.
Citation Information
Patent Citations
Adhesive for compounding stone plates as well as preparation method and application of adhesive
CN116042154A